A REVIEW ON POTENTIAL OF MEDICINAL PLANT: LIMONIA ACIDISSIMA L. (International Association of Biologicals and Computational Digest, 2022)
Plant is an important source of medicine and plays a key role in achieving objectives of WHO for wellbeing of all mankind. People are getting aware about natural products, to fulfil the requirement of medicinal values, Limonia acidissimaL. of family Rutaceae, emerged out to be one of the most valuable plant owing multiple medicinal properties. The main objective of the present study is to recognize and identify different chemical constituents of the plant, which are important in the field of medicine. Hence in this article, the attempt has been made to study literature of different medicinal values, Pharmacological activities and the Ethnobotanical uses of Limonia acidissima L. The complied information of the plant can be used in various medicinal field.
Keywords: Limonia acidissima L., Phytochemicals, Ethnomedicinal, Pharmacological, Medicinal